Application of Realistic 3D Model in Building Prefabricated Nanomaterial Structure. (4th August 2022) - Li, Sihui
Abstract : In order to solve the problem of 3D modeling in building assembly, an application of a 3D model based on the real scene in the building assembly structure is proposed. This method, based on the current BIM technology in nanomaterial design research, analyzes the problems existing in the traditional assembly structure design scheme and analyzes the feasibility of BIM technology in the forward design of assembly buildings from the perspective of theory and practical application. The experimental results show that the urban building model established by the 3D model has high precision and a good real-scene effect. The accuracy of the building model meets the requirements of 1 : 1000 mapping, has measurable accuracy, and elevation accuracy is better than 30 cm. The 3D model promotes the development of informatization.